Effect of Er:YAG and CO2 Lasers with and without Sodium Fluoride Gel on Dentinal Tubules: A Scanning Electron Microscope Examination - (:unkn) unknown (MARY ANN LIEBERT, INC, 2008)
The aim of this pilot study was to evaluate the occluding effect of erbium:yttrium-aluminum-garnet (Er:YAG) and carbon dioxide (CO2) lasers as monotherapy and in combination with topical fluoride gel on human dentinal tubules by scanning electron microscopic (SEM) examination. Materials and Methods: Thirty-six dentine specimens with exposed dentinal tubule orifices were included in this study. The samples were divided into six groups. Group A served as controls, group B was treated with 2% sodium fluoride (NaF) gel alone, groups C and D were irradiated with Er:YAG (30 Hz, 60 mJ, for 10 sec) and CO2 (1 W, continuous-wave mode, for 10 sec) lasers, respectively, and groups E and F received NaF gel plus Er:YAG and CO2 laser irradiation, respectively. Results: Under SEM analysis, numerous exposed, normally-structured dentinal tubule orifices were seen in the control group. Some narrowing of the exposed tubule orifices was seen in group B. A melted, irregular surface structure with small peaks was observed in group C. The surface of group D also had a melted appearance, but a fibrillar deformation of the surface structure was seen on the specimens. However, the surface morphologies seen were remarkably different in groups E and F. While the tubule orifices were obviously occluded but depressed into craters in group E, the surface structure of group F primarily showed a smooth appearance. In terms of numbers and diameters of open dentinal tubules, there was no significant difference between the laser-alone and combination groups, whereas the difference was found to be significant when the control and NaF groups were compared with each other and the remaining laser-alone or combination groups. Conclusion: The dentinal tubules in all laser groups were occluded after laser irradiation, but more marked occlusions were observed when laser and NaF gel were combined.
Keywords: ND-YAG LASER; HYPERSENSITIVE DENTIN; ROOT SURFACES; IN-VITRO; IRRADIATION; VARNISH; SENSATION; VIVO